Efektivitas Kerjasama PPATK dan AUSTRAC dalam Memberantas Tindak Pidana Pendanaan Terorisme di Indonesia Tahun 2014–2017 - Putri, Rr. Nurul Rahmah Cahyo; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
This research was motivated by the increasing incidence of terrorism that threatensglobal security. A terrorism attack can occur because of funding factors where funding forterrorism also categorized into criminal acts which are usually called criminal acts ofterrorism funding. In seeking to eradicate the crime of terrorism funding the Indonesiangovernment cooperated with neighboring countries, in this case the Indonesian governmentthrough the Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK) collaborated withthe Australian Transaction and Analysis Center (AUSTRAC). Both of these institutions areFinancial Intelligence Units (FIUs) that have a vision to combat the crime of money launderingand terrorism funding. This research aims to explain the effectiveness of the cooperationbetween PPATK and AUSTRAC in combating terrorism funding crimes in Indonesia in 2014 -2017. By using the number of Analysis Results (HA) with the alleged crime of financingterrorism issued by PPATK and the number of terrorist acts that occurred in Indonesia as anindicator of the assessment of the effectiveness of the two FIU cooperation, the authorsproduced research findings , that cooperation established by PPATK and AUSTRAC can besaid to be effective in combating terrorism funding crimes in Indonesia in 2014-2017.